2008
DOI: 10.1158/0008-5472.can-08-0197
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone Receptor Levels and Cell Context Affect Tumor Cell Responses to AgonistIn vitroandIn vivo

Abstract: Activation of gonadotropin-releasing hormone (GnRH) receptors inhibits proliferation of transformed cells derived from reproductive tissues and in transfected cell lines. Hence, GnRH receptors represent a therapeutic target for direct action of GnRH analogues on certain proliferating cells. However, more cell biological data are required to develop this particular application of GnRH analogues. Therefore, we compared the effects of GnRH receptor activation in transfected HEK293 cells (HEK293 [SCL60] ) with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 52 publications
2
55
0
5
Order By: Relevance
“…The antiproliferative effects of GnRH-II in endometrial cancer cells may be due to increased apoptosis. Recently, Morgan and colleagues (33) reported that GnRH agonists mediated the inhibition of cell growth by the induction of apoptosis in different cells. This study also showed that GnRH receptors and intracellular signaling play an important role in the apoptotic process, contributing to the cell type-specific effects of GnRH on growth.…”
Section: Discussionmentioning
confidence: 99%
“…The antiproliferative effects of GnRH-II in endometrial cancer cells may be due to increased apoptosis. Recently, Morgan and colleagues (33) reported that GnRH agonists mediated the inhibition of cell growth by the induction of apoptosis in different cells. This study also showed that GnRH receptors and intracellular signaling play an important role in the apoptotic process, contributing to the cell type-specific effects of GnRH on growth.…”
Section: Discussionmentioning
confidence: 99%
“…The second and third intracellular loops are important for receptor-G protein interaction and signaling functions in GPCRs. Differences in the levels of GnRH receptor affect the GnRH-stimulated production of inositol phosphate within cells and contribute to the cell type-specific effects of GnRH (Morgan et al 2008). A specific alanine residue is involved in certain GPCRs, the equivalent of which is Ala-261 in the GnRH receptor.…”
Section: Ligand Receptor-mediated Intracellular Signal Transduction Imentioning
confidence: 99%
“…The possibility is that differences in the levels of GnRH receptor expression exist during cell passage in vitro or as a result of varied culture conditions. Consequently, differences in levels of GnRH receptor and signaling pathway individually contribute to the induction of apoptosis and play an important role in the regulation of GnRH on cell typespecific growth (Morgan et al 2008).…”
Section: Gnrh and Apoptosismentioning
confidence: 99%
“…A direct relationship has been found between this effect of GnRH agonists and the level of GnRH receptor expression in the particular cell line. (Morgan et al, 2008) Modifications that retard the dissociation rate of the GnRH analog from its receptor have been shown to increase its biopotency and bioavailability in vivo, which are highly dependent on the peptide's stability and permeability across biological membranes. In spite of extensive research in the field of hormonal therapy and development of various GnRH agonists over the past three decades, GnRH peptide analogs still suffer from poor pharmacokinetic properties.…”
Section: Introductionmentioning
confidence: 99%